DEVELOPING INDICATORS TO MEASURE SUSTAINABLE MARINE TOURISM DEVELOPMENT STUDY CASE: IN SELONG BELANAK VILLAGE, WEST PRAYA, CENTRAL LOMBOK PROVINCE - Rumiati, Agnes Tuti; Gunawan, Janti; Ekasari, Nazihah (PEOPLE: International Journal of Social Sciences, 2019)
Tourism has been selected as one of the strategic sectors to reach Indonesia sustainable development goals. Land, marine, cultural, and other type of tourism have been developed, but importantly, Indonesia tourism development has been driven mostly by government strategic decision, as it relates with infrastructure. Although Indonesia is a country with the third longest coasts in the world, however, the coastal tourism is less developed. Beside infrastructure, coastal tourism is more complex because it relates to access of both land and water, with more diverse community. The tourism management study stresses that development indicators are necessary to manage the process of shifting one economy, such as fishing or farming village, toward sustainable tourism based economy. It requires the integration of policy, implementation, evaluation and community feedbacks. This study proposes indicators to measure coastal tourism in Indonesia, which covers 11 indicators that reflects the dimensions of sustainable tourism. Cluster analysis is used to group the indicators, and the indicator is developed and tested at Selong Belanak village, a costal tourism in Lombok, Indonesia.